2016
DOI: 10.3390/nu8120828
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and Dementia Risk: Consideration through a Cerebrovascular Perspective

Abstract: A number of natural and chemical compounds that exert anti-oxidative properties are demonstrated to be beneficial for brain and cognitive function, and some are reported to reduce the risk of dementia. However, the detailed mechanisms by which those anti-oxidative compounds show positive effects on cognition and dementia are still unclear. An emerging body of evidence suggests that the integrity of the cerebrovascular blood-brain barrier (BBB) is centrally involved in the onset and progression of cognitive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 145 publications
(160 reference statements)
0
13
0
Order By: Relevance
“…Besides the presented roles, Vit C has also been suggested to prevent neurodegenerative changes and cognitive decline by protecting blood–brain barrier (BBB) integrity [ 68 ].…”
Section: Role Of Vitamin C In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Besides the presented roles, Vit C has also been suggested to prevent neurodegenerative changes and cognitive decline by protecting blood–brain barrier (BBB) integrity [ 68 ].…”
Section: Role Of Vitamin C In Neurodegenerative Diseasesmentioning
confidence: 99%
“…So far, scant investigations have explored the effects of anti-oxidative vitamins on dementia through the cerebrovascular axis [ 95 ]. The study of Kook et al [ 87 ] recently reported that high-dose supplementation of AA reduced amyloidosis in AD mice (5XFAD) via the reduction of BBB disruption and mitochondrial alteration [ 96 ].…”
Section: Ascorbic Acid and Its Relevance To Alzheimer’s Diseasementioning
confidence: 99%
“…To date, AA seems to offer neuroprotection by restoring BBB integrity. However, further investigations should focus on simultaneously testing brain neuroprotective effects and BBB protective effects of antioxidants [ 95 ]. AA seems to possess both types of neuroprotection and could be further tested as a targeted dual agent for preventing cognitive decline.…”
Section: Ascorbic Acid and Its Relevance To Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that natural compounds, which act as antioxidative, have positive effects on neuroprotection. [13] Some TCM contain contributing factors as mentioned above on preventing dementia, such as AChE inhibitors and neuronal injury inhibitors. Part of the TCM also exhibit anti-in ammation, anti-hypertension, anti-hyperlipidemia, anti-diabetes, and anticonvulsion characteristics.…”
Section: Discussionmentioning
confidence: 99%